Impact of Weed Control by Hand Tools on Soil Erosion under a No-Tillage System Cultivation. - Blanco-Sepúlveda, Rafael; Aguilar-Carrillo, Amílcar; Lima-Cueto, Francisco Javier (MDPI, 2021)
In conservation agriculture, the no-tillage cultivation system and the retention of permanent vegetal cover are crucial to the control of soil erosion by water. This paper analyses the cultivation of maize under no-tillage, with particular reference to the effect produced on soil erosion when weed control is performed by a hand tool (machete), which disturbs the surface of the soil, and to the behavior of the soil cover in these circumstances. The study area is located in the humid tropical mountains of northern Nicaragua (Peñas Blancas Massif Nature Reserve). The results obtained show that 59.2% of the soil surface was affected by appreciable levels of sheet and splash erosion, although the vegetal cover of the soil was relatively high (with average weed and litter cover of 33.9% and 33.8%, respectively). The use of machetes for weed control provoked considerable soil disturbance, which explained the high rates of erosion observed. Moreover, this form of soil management disturbs the litter layer, making it less effective in preventing erosion. The litter remains loose on the soil surface, and so an increase in soil cover does not achieve a proportionate reduction in the area affected by erosion; thus, even with 80–100% weed and litter cover, 42% of the cultivated area continued to present soil erosion.
Keywords: Suelos - Erosión; Water erosion; Conservation agriculture; No-tillage; Weed control by hand tool; Ground vegetal cover